Pengaruh Hubungan Kerja dan Komunikasi Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Bandar Lampung - Hendri Dunan; M Yogi Syahputra (Jurnal EMT KITA, 2023)
The Department of Population and civil registration of Bandar Lampung city faces a problem, namely the lack of good cooperation that can cause duplicate data and lack of communication that can affect employee performance. The problems of this study are: whether the employment relationship affects employee performance, and whether communication affects employee performance. This study aims to determine the effect of Labor Relations and communication on employee performance. The method used quantitative methods with causal associative. The sample studied 112 respondents. Work relationship (X1), and communication (X2), and employee performance (Y). Source data obtained from the questionnaire given to employees. Tested with the SPSS application, the results showed that work relationships and communication significantly and strongly influence employee performance. Labor Relations significantly affect employee performance, with significance (5.902)>(1.98197), and sig. 0,000<0,05. Communication has an influence on employee performance, with (6,256)>(1.98197), and sig. 0,000<0,05. As well as work relationships and communication contribute to employee performance.